2nd International Conference on Molecular Diagnostics and Biomarker Discovery (MDBD) - Noordin, Rahmah (Institute for Research in Molecular Medicine, 2017)
This MDBD 2017 conference promises to be an exciting event with thirteen invited speakers from various parts of the world - Spain, Iran, USA, Saudi Arabia, Singapore, Australia, Brazil, Germany and Malaysia. The conference is themed “Advances in Biomarker Discovery and Technologies for Better Diagnostics”